A study to evaluate the change in perfusion index as an indicator of successful ultrasound-guided supraclavicular block - Jatin Lal (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Perfusion index (PI) is a new simple, objective and non-invasive method for evaluation of the success of central neuraxial and peripheral nerve blocks. So, we conducted a study with an aim to evaluate PI as an indicator for success of ultrasound-guided supraclavicular block (SCB). Methods: 65 patients of either sex, age 18–60 years, American Society of Anesthesiologists physical status I and II posted for upper limb surgery under ultrasound (US)-guided SCB were included. PI was recorded at baseline every 2 minutes till 10 minutes and then every 5 minutes till 30 minutes after block. PI ratio was calculated as the ratio between PI at 10 minutes and baseline PI. Sensory and motor blocks were assessed at 5-minutes intervals up to 30 minutes. Descriptive analysis was applied by mean and standard deviation for quantitative, frequency and proportion for categorical variables. Results: Mean PI increased continuously from baseline and reached the maximum at 10 minutes and then slightly decreased up to 30 minutes, but values at subsequent time intervals were quite high as compared to baseline. In case of successful blocks, median PI started increasing 2 minutes after the block and then increased in a linear fashion till 10 minutes, whereas in case of failed blocks, it only increased minimally. Conclusion: PI is an objective and faster indicator for evaluating success of US-guided SCB. A cut-off value of 3.25 for PI and 3.03 for PI ratio showed a fairly good ability with high sensitivity and specificity for predicting the success of SCB.